PENGEMBANGAN LKPD BIOLOGI BERBASIS LINGKUNGAN SEKITAR UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA SMA - Merti Triyanti; Usman Nulhakim (Jurnal Perspektif Pendidikan, 2021)
This study aims to develop environmental-based worksheets to increase motivation and interest in learning for high school students and a description of students' learning difficulties in biology class X SMA Negeri 7 Lubuklinggau. The research method used is Research and development. The sample of this research is 30 students. Data collection techniques in this study used interviews, observations and documents. The data analysis used is data reduction, data presentation and conclusion drawing. The results showed that the LKPD developed was suitable for use by high school students of Class X and there were difficulties in learning biology on environmental pollution materials. This learning difficulty is caused by the difficulty in understanding the material presented in the teaching materials. In addition, learning difficulties experienced by students are also triggered by low learning motivation caused by not being interested in biology lessons, inappropriate teaching techniques, facilities and infrastructure, and inadequate learning resources